Improving Mosque Management: Strategies Towards A Center For Islamic Activities - Mohammad Amin; Siti Muhammadah (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This research focuses on the transformation of mosque management as a center of modern Islamic activities, with the aim of identifying the main factors that support the success of mosque management in responding to the needs of worshippers and the challenges of the times. This study uses a qualitative approach with a case study method, involving direct observation, in-depth interviews, and documentation analysis to collect data from mosque administrators, worshippers, and related stakeholders. The results of the study show that the success of mosque management transformation is influenced by four main elements: adaptive organizational structure, sharia-based financial transparency, the use of digital technology, and active community participation. The use of technology speeds up administration and increases accountability, while congregational involvement enriches the dynamics of religious and social programs. This research implies that mosque administrators need to develop managerial and digital capacity in a sustainable manner to maintain the relevance of mosque institutions in the midst of social change. In addition, public policy support that strengthens synergies between mosques, educational institutions, and philanthropic organizations can accelerate innovation and expand the social impact of mosques. This study provides recommendations for further studies with a quantitative approach to measure the impact of transformation more broadly and deeply. This finding is expected to be the basis for the development of a sustainable mosque management model that is oriented to the needs of modern society.